Neuregulin-4 is associated with plasma glucose and increased risk of type 2 diabetes mellitus (Swiss Medical Weekly, 2019)
BACKGROUND Neuregulin-4 is a cytokine with many functions and is primarily produced by fat tissue. AIM OF THE STUDY The aim of the study was to observe the relationship between serum neuregulin-4 levels and diabetes regulation in type 2 diabetes mellitus (T2DM), and to compare neuregulin-4 levels of diabetic subjects with those in healthy controls. METHODS Patients with T2DM were included to the study. Healthy subjects were enrolled as controls. Subjects with T2DM with glycated haemoglobin (HbA1c)